Ultra-confined surface phonon polaritons in molecular layers of van der Waals dielectrics - Dubrovkin, Alexander M. (2018)
Improvements in device density in photonic circuits can only be achieved with interconnects exploiting highly confined states of light. Recently this has brought interest to highly confined plasmon and phonon polaritons. While plasmonic structures have been extensively studied, the ultimate limits of phonon polariton squeezing, in particular enabling the confinement (the ratio between the excitation and polariton wavelengths) exceeding 102, is yet to be explored. Here, exploiting unique structure of 2D materials, we report for the first time that atomically thin van der Waals dielectrics (e.g., transition-metal dichalcogenides) on silicon carbide substrate demonstrate experimentally record-breaking propagating phonon polaritons confinement resulting in 190-times squeezed surface waves. The strongly dispersive confinement can be potentially tuned to greater than 103 near the phonon resonance of the substrate, and it scales with number of van der Waals layers. We argue that our findings are a substantial step towards infrared ultra-compact phonon polaritonic circuits and resonators, and would stimulate further investigations on nanophotonics in non-plasmonic atomically thin interface platforms.